A Study on Effect of Laughter on Pulmonary Functions among Elderly People (Academia Journal of Medicine, 2021)
Background: Laughter Yoga has become a very popular form of exercise and is primarily practiced in groups. Laughter is initially forced as a physical exercise by maintaining eye contact with other members in the group and promoting childlike playfulness. This soon leads to real, spontaneous laughter. Laughter Yoga is the one only technique that allows adults to achieve sustained hearty laughter without involving cognition. The objective is to study the effect of laughter on pulmonary functions in elderly people. Subjects and Methods: This study was done under ICMR STS research Programmed for Undergraduate students at Dr D Y Patil Medical College, Pune from June 2016 to October 2016. A total of 60 study subjects aged more than 60 years of age were selected for the purpose of the study. The Pulmonary functions were tested by using instrument ‘Spirotech before and after the laughter therapy for 4 weeks. Results: Immediately after a good bout of laughter FVC and PEFR were increased but not statically significant FEV1 was statically significant immediately after good laughter. All three pulmonary functions FVC, FEV1 and PEFR were statically highly significant after regular laughter therapy practice for 4 weeks. Conclusion: Laughter is beneficial for pulmonary functions when practiced regularly in our study laughter therapy for 4 weeks proved beneficial ruling out all age sex and ethnic differences.
Keywords: Pulmonary Function; Laughter Therapy; Yoga; Spirometry; Spirometry Old Age